PENERAPAN INKUIRI MORAL BERBASIS NILAI-NILAI KEARIFAN LOKAL MINANGKABAU “ALAM TAKAMBANG JADI GURU” UNTUK PEMBENTUKAN KARAKTER SISWA - ronald fransyaigu (Jurnal Inovasi Sekolah Dasar, 2015)
Abstract: This study was aim at analyzing the implementation of moral inquiry method in integrating the values of local wisdom Minangkabau society that used to form the character of the students in learning Citizenship Education in elementary school. This study used a qualitative approach with classroom action research methods and data obtained through observation, interviews, and observation sheets attitude. Subjects in this study were teachers and students of class V elementary school 18 Air Tawar Padang. Data analysis techniques used were data reduction, data presentation, drawing conclusions / verification. Results of the study revealed that the implementation method based on local wisdom moral inkuri Minangkabau to the character formation of students showed a good increase from the initial data obtained prior to action. Preliminary data indicated that the majority of students were in the stage of "Start Seen" for each character and the third cycle are in the stage of "entrenched" for each character, the average occupied 24 students from 28 students. The use of moral inquiry method can make the learning was presented in a concrete and contextual by providing moral discourse then learners find their own settlement discussions in accordance with the rules agreed upon in the formation of character. Keywords: Moral Inquiry, Citizenship Education Learning, Character Education, Local Wisdom Minangkabau